(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2026)
Enugu State is one of the major economic centers in south eastern Nigeria which has a substantial informal sector as an employer, income and local trade but its activities are not controlled leading to derailment of the overall growth plans. Based on secondary data about surveys conducted in the country, scholarly literature, policy-related documents published between 1970 and 2025, this article is exploring the contribution of the sector to the gross state product, employment generation, and poverty alleviation rate, cancelling it at 55-65 percent of economic output in Enugu. The examples of positive dynamics entail resilience in the crises such as the 2023 naira redesign and the Covid-19, and the negative factors are low productivity, tax avoidance, and poor formal connections. Literature gaps covered in the study are specific to Enugu, which dwells on the dominance of trade based on the market and gender disparities in participation. Issues such as structural shortfall and absence of policy inclusion are also discussed and solutions that include progressing to formalization in bits, availing microfinances and skills training have been recommended to boost sustainable development. This acculturation can make Enugu more competitive, and the development can be inclusive though reforms in the economy of the country.